Running a Fragment Shader on a GPU Core. (Communications of the ACM, 2008)
The article discusses the efficient execution of fragment shrader on a single-core graphics processing unit (GPU), detailing shrader compilation to SIMD (single instruction, multiple date) instruction sequences. Shrader compilation by the graphics driver produces a GPU binary from high-level fragment shrader source, the article states. Topics include four vector registers, GPUs executing a copy of the shrader binary on each of the four thread contexts, and a pool of general-purpose vector registers.